(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This text explores the potential of artistic-pedagogical practices in the context of incarceration, taking the activity notebook Das saídas que moram nas palavras as a starting point. Theater and writing are thus investigated as possible abolitionist practices, which transcend walls, opening windows to other glimpses of freedom.